Use of double filtration plasmapheresis for the treatment of acquired thrombocytopenic thrombotic purpura. Issue 6 (11th February 2020) - Chauvel, Femie; Reboul, Pascal; Cariou, Sylvain; Aglae, Cédric; Renaud, Sophie; Trusson, Rémi; Garo, Florian; Ahmadpoor, Pedram; Prelipcean, Camelia; Pambrun, Emilie; Moranne, Olivier
Abstract: Double filtration plasmapheresis (DFPP) could be an alternative method to simple plasma exchange plasmapheresis in the treatment of acquired thrombotic thrombocytopenic purpura (aTTP). In a retrospective single center case series, we studied clinical presentation, management care, and prognosis of aTTP patients from our academic center treated with DFPP and IV infusion of fresh frozen plasma (FFP) between 2009 and 2018. Nine patients were included for 11 episodes. Median age was 38 years old (IQR 26‐53) with 78% women. Six episodes (55%) required admission to the ICU, four of which required mechanical ventilation. Median FFP volume transfused was 35.2 mL/kg/d of session. Response was complete for nine episodes (82%). Four patients presented an early relapse, two a late relapse. Four patients died: one had an active untreated HCV infection, and two were over 80‐year‐old polymorbid patients. DFPP seems to be an efficient method of therapeutic plasmapheresis in TTP when combined with FFP transfusion and immunosuppressive treatments.